2022
DOI: 10.1289/ehp9824
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to PM2.5 during Pregnancy and Fetal Growth in Eastern Massachusetts, USA

Abstract: Background: Prior studies have examined the association between fine particulate matter [PM in aerodynamic diameter ( )] and fetal growth with either limited spatial or temporal resolution. Objectives: In this study, we examined the association between exposure during pregnancy and fetal growth measures (ultrasound parameters and birth weight) in a pregnancy cohort using spatiotemporally resolved in Eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
1
9
1
Order By: Relevance
“…Yuchi et al found that road proximity was associated with incidence of Alzheimer’s disease, and this association may be partially mediated by air pollution [ 27 ]. Michael et al also reported that higher gestational exposure to PM 2.5 exposure in the first 16 wk was associated with smaller fetal growth measures, where associations were particularly strong for biparietal diameter (BPD), abdominal circumference (AC), and birth weight [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yuchi et al found that road proximity was associated with incidence of Alzheimer’s disease, and this association may be partially mediated by air pollution [ 27 ]. Michael et al also reported that higher gestational exposure to PM 2.5 exposure in the first 16 wk was associated with smaller fetal growth measures, where associations were particularly strong for biparietal diameter (BPD), abdominal circumference (AC), and birth weight [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with four studies that have assessed the impacts of prenatal PM 2.5 exposure across averaged time windows on in utero fetal growth [ 34 , 38 40 ]. Leung et al assessed spatiotemporal modeled PM 2.5 exposure and fetal growth among predominately non-Hispanic white participants in Eastern Massachusetts [ 39 ]. They found average PM 2.5 from conception through 16 weeks of gestation was associated with reduced abdominal circumference measured at both < 24 weeks and 24 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[ 80 ]). A very recent study showed that higher exposure to PM 2.5 in the first 16 weeks of pregnancy was associated with a significantly lower birth weight among other smaller fetal growth measures [ 81 ]. These observations may have a particular resonance in the context of the early origins of COPD.…”
Section: Air Pollution As An Early Determinant Of Copdmentioning
confidence: 99%